Clinical Evaluation of Body Composition, Diet, and Physical Activity in Type 1 Diabetes: A Controlled Cross-Sectional Study - Isaki Hanamura; Ryoko Hongo; Norio Abiru; Nobuko Sera (Diabetology)
Background: This study examined differences in body composition, dietary intake, and exercise habits between people with type 1 diabetes (T1DM) and those without diabetes (NDM). We also sought to clarify the clinical and lifestyle characteristics of overweight people with T1DM. Methods: This controlled cross-sectional study was conducted at a single center, and included 45 people with T1DM and 50 NDM individuals. Body composition, nutrient intake, and exercise habits were evaluated, and exercise habits were compared between people with a T1DM onset before 20 years of age and those with an onset at or after 20 years of age, in relation to the NDM group. Overweight was defined using a BMI of 25.0 kg/m2 as the cutoff. Results: The T1DM group had significantly higher BMI and body fat than the NDM group, but no significant difference in muscle mass, and consumed a higher percentage of carbohydrates and a lower percentage of fat. The early-onset T1DM group had significantly lower exercise habits during their school years and in their current life than the NDM group. Individuals in the overweight T1DM group had a lower time in range on a continuous glucose monitor and a higher carbohydrate intake than those in the non-overweight T1DM group. Conclusions: The study suggested that the T1DM group had a significantly higher body fat percentage and carbohydrate intake, and significantly reduced exercise habits as students, compared to the NDM group.